An Evaluation of MINDFIT-A Student Therapeutic Running Group as a Multi-Layered Intervention in the United Kingdom - Jan Gurung; James Turner; Elizabeth Freeman; Charlotte Coleman; Susan Iacovou; Steve Hemingway (MDPI AG, 2023)
Background: Mental health is an ever-increasing concern for UK Universities and is underreported. Creative and dynamic approaches to tackle student wellbeing are important. In 2018, Sheffield Hallam University (SHU) Student Wellbeing Service initiated a pilot study of a therapeutic running programme 'MINDFIT' that combined physical activity, led by a counsellor, alongside a psychoeducation approach to support student mental health. Methods: Mixed methods were used which included the Patient Health Questionnaire-9 (PHQ-9), evaluating low mood and depression, and Generalized Anxiety Disorder Scale-7 (GAD-7), evaluating levels of anxiety. Results: A total of 28 students were triaged onto a weekly programme over three semesters. Overall, 86% of the participants completed the programme. A promising reduction in the scores for PHQ-9 and GAD-7 was found at the end of the programme. Focus groups, with student participants, were held to gather qualitative data for analysis. After thematic analysis, three main themes emerged: "Creating a safe community", "Making progress" and "Pathways to success". Conclusions: MINDFIT was an effective and engaging multi-layered therapeutic approach. Recommendations identified the importance and effectiveness of the triage process in recruiting students and sustainability of the programme through the continued engagement of students post programme. More research is required to identify the long-term effects of the MINDFIT approach and how applicable it is to higher education contexts.